Injury patterns among national-level athletes in Lebanon: a retrospective study - El Osta, L.; El Helou, A.; Hatem, H. A.; El Osta, N. (Research in Sports Medicine, 2022)
Objectives This study aims to assess the annual prevalence, associated factors, and characteristics of musculoskeletal disorders among Lebanese national-level athletes.